Mediating effects of indigenous oil firms' participation and backward linkages on the relationship between local content policy and job creation: Insight from Nigeria - Abdulkabir N. Adedeji; Shaufique F. Sidique; Azmawani Abd Rahman; Siong H. Law (Cogent Business & Management, 2018)
The increase in indigenous oil firms' participation (IOFP) and backward linkages through which additional jobs could be created was the main target of the local content policy (LC policy) implemented in the Nigerian oil sector over the past decade. Thus, the purpose of this paper is to assess whether IOFP and backward linkages mediate the relationship between the LC policy and job creation in the country's oil sector on which there was little empirical research. Data obtained from Nigerian indigenous oil service firms through self-administered questionnaires were analysed by using a bootstrapping technique. Our results revealed that there was an indirect effect of the LC policy on the creation of new jobs. This finding sheds light on the positive impact of the LC policy. Our results imply that if Nigeria's LC policy is effective and efficient, increased job opportunities will follow. This may speed up the country's vision of 2020 on value-addition in achieving economic development through the oil sector.
Keywords: 650